A novel route for the flexible preparation of hydrocarbon jet fuels from biomass-based platform chemicals: a case of using furfural and 2, 3-butanediol as feedstocks. Issue 9 (6th April 2018) - Cui, Xingkai; Zhao, Xuebing; Liu, Dehua
Abstract : Flexible production of hydrocarbon jet fuels with biomass-derived furfural and 2, 3-butanediol as feedstocks by a combination of acid-catalyzed dehydration, aldol condensation, and hydrodeoxygenation. Abstract : Herein, a novel route for the production of renewable hydrocarbon jet fuels from the biomass-derived platform chemicals furfural and 2, 3-butanediol (BD) was developed. Carbonaceous solid acids bearing –SO3 H groups were prepared from biomass or its isolated polymeric components to catalyze the dehydration of BD to methyl ethyl ketone (MEK) in the liquid phase at low temperatures (<170 °C). Lignocellulose, cellulose, and lignin were more suitable feedstocks than xylan to prepare cabonaceous solid acids for well introducing –SO3 H groups into carbon carriers with good acidity. The highest MEK yield of 57.6% with 79.1% BD conversion and 72.8% MEK selectivity was obtained when sugarcane bagasse solid acid with p -toluenesulfonic acid (PTSA) was used as the catalyst. However, the main side product in the dehydration process was cyclic hydrophobic ketal (CHK), formed by the condensation of BD and MEK, and it could be easily re-converted to BD and MEK via acid catalysis. The C9/C14 precursors were obtained by carbon chain extension via aldol condensation of furfural and MEK under alkaline conditions. The product profile could be easily controlled by adjusting the reaction variables, particularly the ratio of furfural to MEK, as well as the solvent system to maximize the yield of the desired C9/C14 precursors and minimize the formation of heavier condensation products. Under the optimal reaction conditions, nearly 100% conversion of furfural with a C9/C14 yield of 99.8% was obtained. Hydrodeoxygenation of the precursors resulted in the formation of hydrocarbon fuels, with C1–C4, C5–C8, and C9–C14 alkane products obtained in the yields of 15.4%, 7.9%, and 73%, respectively. This process showed a theoretical exergy efficiency similar to that of the bioethanol process and higher than that of the biobutanol process.